The accomplice : a novel - Lutz, Lisa (Ballantine Books, 2022)
"Owen's wife was murdered. His best friend, Luna, found the body. Everything and everyone is thrown into question in this riveting suspense novel from the New York Times bestselling author of The Passenger. Owen is rich, charming, and chronically dissatisfied. His life is forever entangled with Luna Grey, his no-nonsense best friend who is struggling to hide her dark past. From the fateful day they meet in college, the two become inextricably linked. They can't be mentioned without the other: Owen and Luna, Luna and Owen. In addition to their own trove of personal secrets, there is the deadly one they share. It forges a bond that will last decades. Years later, Owen disappears on his wife, Irene, for hours, mostly to spend time drinking with Luna. Luna is now an assistant to the eccentric and reclusive artist Leo Whitman, who also happens to be Irene's stepfather. But when Irene is found dead, the victim of a brutal crime, it unleases a torrent of secrets from the past as well as everything they would have preferred to have kept hidden in the present. Despite their innocence, the murder causes the walls to quickly close in around them. The Accomplice examines the intense relationship between two very different misanthropic best friends. What happens when one of them takes a sledgehammer to their bond and the other lights that wreckage on fire? If secrets are what kept Owen and Luna together, they just might tear them apart, too. If they let them"--